An Intelligent Management System of Instruments and Equipment Based on Power Line Communication. (February 2019) - Li, Bao; Xia, Huangrong; Kuang, Haoxin; Jin, Wen; Wang, Qiang; Su, Feng; Li, Dongxing; Yan, Meichen
Abstract: Instruments and equipment are an important fixed asset of companies and public institutions nowadays, which do not only need to be preserved in value but are also relied on to create more value. However, at present, the management of instruments and equipment is mainly based on manual statistics, sometimes with the help of QR codes to improve the efficiency. With this kind of management method, the statistics collected are oftentimes incomplete and untimely, resulting in repeated investment and a waste of resources. The intelligent management system based on power line communication designed in this solution can collect the device data comprehensively in real-time and form a report, providing data support for the decision-making of the management. Power lines are used as the communication path, so that no extra wire are needed to be deployed and cost can be reduced effectively. The system can comprehensively solve the problems that currently exist in the management of instruments and equipment.